Compliance in The Micro, Small and Medium Enterprises (MSMEs) Taxes and Reviewed From an Islamic Perspective - Kurniawan, Indra; Kuntadi, Cris; Izni Shafie, Dalili (IKONOMIKA, 2023)
Tax compliance is the government's goal to achieve the expected tax targets. To achieve this compliance, the government offers a low tax rate to encourage MSMEs to pay its tax debt. On the other hand, taxes are burdensome for MSMEs because they are government expenditures that are deducted from net income so taxpayers look for ways to reduce the taxes paid . This article reviews the influence of income turnover, self-assessment system also tax amnesty on taxpayer compliance with micro, small and medium enterprises , a study of tax accounting literature. Meanwhile From an Islamic perspective, each taxpayer has the responsibility to pay the taxes. The taxpayer compliance in Islamic perspective stated that governments permitted to take some of its citizen’s assets such the taxes. This can be seen in the Hadith recounted by Fatimah bint Qais and Q.S At-Taubah 29. This article aims to develop the hypothesis according connection among variables for further study. This research show several findings, there are: 1) Income Turnover influences Taxpayer Compliance ; 2) The Self Assessment System influences Taxpayer Compliance ; and 3) Tax Amnesty affects Taxpayer Compliance.